2003
DOI: 10.1029/2002jc001570
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐shore sediment transport and the equilibrium morphology of mudflats under tidal currents

Abstract: [1] We describe a mathematical model of suspended sediment transport under cross-shore tidal currents on an intertidal mudflat. We employ a Lagrangian formulation to obtain periodic solutions for the sediment transport over idealized bathymetries and use these to investigate the process of settling lag. In deep water away from the shoreline the concentration of suspended sediment tends to a constant value, and we may invert the relation between bathymetry and offshore concentration to estimate how the gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 33 publications
(106 reference statements)
5
78
0
1
Order By: Relevance
“…In particular, the characteristic convex profile described theoretically by Friedrichs and Aubrey (1996) and empirically by Kirby (2000) is reproduced, and the flats are found to have a tendency to accumulate sediment over long times. We find that the cross-shore width of the flats is almost independent of tidal range, and increases with sediment supply, as predicted by Pritchard and Hogg (2001). We have found that flood-or ebb-dominated tides lead to a steeper equilibrium profiles, and that ebb-dominance may lead to a flat which retreats over long times.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…In particular, the characteristic convex profile described theoretically by Friedrichs and Aubrey (1996) and empirically by Kirby (2000) is reproduced, and the flats are found to have a tendency to accumulate sediment over long times. We find that the cross-shore width of the flats is almost independent of tidal range, and increases with sediment supply, as predicted by Pritchard and Hogg (2001). We have found that flood-or ebb-dominated tides lead to a steeper equilibrium profiles, and that ebb-dominance may lead to a flat which retreats over long times.…”
Section: Discussionsupporting
confidence: 57%
“…The model which we develop is an extension of that of Roberts et al (2000), including more complete dynamics, and integrated using a numerical method (canute) which has been designed to represent the dynamics accurately in very shallow water, in order to avoid the physically unrealistic velocities seen by Roberts et al We compare our results with analytical predictions, obtained by extending the work of Friedrichs and Aubrey (1996), which are described in more detail elsewhere (Pritchard and Hogg, 2001). …”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations